2021
DOI: 10.7861/fhj.2020-0207
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition education in core medical curricula: a call to action from tomorrow's doctors

Abstract: In recent years lifestyle interventions have gained traction as increasingly useful ways to promote health among the population. Within these changes, nutrition remains paramount. We aimed to present an overview of the current status of nutrition education in UK undergraduate medical curricula, highlighting pockets of innovative teaching, alongside areas for improvement. Nutrition competency is outlined in General Medical Council Outcomes for Graduates, increasingly featured in mainstream headlines and relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…However, this requires commitment from curriculum designers to support their staff and organise its delivery and evaluation 34 . Progress has been made by some UK medical schools including University College London Medical School, which has included a culinary medicine course within its core curriculum involving culinary skills training, case‐based discussions and motivational interviewing role play 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this requires commitment from curriculum designers to support their staff and organise its delivery and evaluation 34 . Progress has been made by some UK medical schools including University College London Medical School, which has included a culinary medicine course within its core curriculum involving culinary skills training, case‐based discussions and motivational interviewing role play 35 …”
Section: Discussionmentioning
confidence: 99%
“…34 Progress has been made by some UK medical schools including University College London Medical School, which has included a culinary medicine course within its core curriculum involving culinary skills training, case-based discussions and motivational interviewing role play. 35 Most interventions included non-medical professionals as instructors (n = 11); however, only four were explicit in utilising IPL. 19,21,24,27 The latest BEME report on the effects of IPL found that it improves the effectiveness of educational interventions.…”
Section: Discussionmentioning
confidence: 99%
“… 52 Often nutrition may be included as cocurricular or extracurricular activities, such as student-selected components, elective courses, research projects or external opportunities through student society-led groups such as Nutritank. 53 Currently, medical doctors report rarely including nutrition in clinical care, with various cited reasons including time and confidence. 29 In part this is likely due to a lack of nutrition education in their own training.…”
Section: Discussionmentioning
confidence: 99%
“…The place of nutrition in medical curricula has been reported as being peripheral (52) . Often nutrition may be included as co-curricular or extracurricular activities, such as student selected components, elective courses, research projects or external opportunities through student society-led groups such as Nutritank (53) . Currently, medical doctors report rarely including nutrition in clinical care with various cited reasons including time and confidence (29) .…”
Section: Challengesmentioning
confidence: 99%